The power of community how phenomenal leaders inspire their teams, wow their customers, and make bigger profits - Partridge, Howard (McGraw Hill-Ascent Audio, 2018)
Boost engagement-and profits-by feeding your staff's craving for community It seems the more connected we are through email, smart phones, and social media, the more disconnected we become on a personal, human level-and teamwork suffers tremendously. If this is happening in your company, fear not. The solution is here. The Power of Community provides a step-by-step approach to transforming your organization by tapping into the human need to connect with and feel valued by others. By creating a company culture based on core community values, you'll empower your workforce, build customer loyalty, and drive profits and growth. This game-changing guide describes why "community" is the answer to employee disengagement-which is now at a record 70 percent-and it explains how to develop the kind of culture that makes an industry leader of your business. It takes hard work and determination, but the rewards will astound you. "When people feel like they belong to one another, when they feel cared for, and they believe that the vision is worth sacrificing for, they will go the extra mile for the company," the author writes. This is true community, and it's at the core of today's most successful companies. Business leaders often tell their people, "We're all in this together," but very few follow through on this sentiment. Separate yourself from the pack by implementing the simple but profoundly effective methods in this book. When people feel they're part of something bigger than themselves, they're more collaborative, creative, and innovative-and this will always drive organizational success. Everyone wins in The Power of Community